Social Media Usage and Stock Return: The Mediating Role of Profitability - Mody Kusumatuti, Febriyanti; Ghofar, Abdul; Widya Prihatiningtias, Yeney (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This study aims to determine the effect of social media usage on stock returns and the role of profitability as a mediating variable. Methodology/approach: This study uses a quantitative approach. The population in this study were consumer non-cyclical sector companies listed on the Indonesia Stock Exchange in 2020-2023. The sampling technique used was purposive sampling and 31 companies were obtained with an observation period of 4 years, resulting in 124 sample units in this study. Findings: The results showed that the social media usage had a positive effect on stock returns, but profitability was unable to mediate the positive effect of social media usage on stock returns. Practical implications: The results of this study can provide strategic insights to consumer non-cyclical companies regarding the maximization of social media usage by companies. This aims to see the dynamics of social media which will ultimately affect the company's stock returns. Originality/value: Research related to impression management on social media and stock returns has not been widely conducted. Research with similar themes was conducted in the previous decade so it can be indicated that it is less relevant to current conditions. The research is a development of previous research that separately tested the use of social media on profitability and profitability on stock returns. Therefore, this study uses a mediating variable of profitability with a proxy for return on assets. This study also adds one category of impression management, namely financial achievement Keywords: Social Media; Stock Return; Profitability